Histopathological study of non-neoplastic skin lesions in a tertiary care center - Dr. Sridevi Vijayasankar; Dr. Lionel Rohit Mathew; Dr. Ezhilvizhi Alavandhar; Dr. C.S. Vijayalakshmi (Tropical Journal of Pathology and Microbiology, 2020)
Introduction: Skin is the largest organ of our body. Non-neoplastic skin lesions are more common than neoplastic lesions. The histopathological study was done to know the prevalence of various non-neoplastic skin lesions of patients who attended the outpatient department of dermatology over a period of three years from Jan 2016-Dec2018. The present study was based on the histopathological presentation of various non-neoplastic skin lesions, their prevalence, and classifying the lesions into various categories. Materials and Methods: In this study total of 209 cases of skin lesions were taken over a period of three years. The diagnosis of these skin lesions was confirmed by histopathological examination with routine hematoxylin and eosin stain. Results: A total of 209 cases of non-neoplastic lesions were taken for the study. Out of these lesions, 63 cases (30.14 %) were non-infectious - vesiculobullous, 54 ( 25.84 %) were reported under the category of infectious etiology, 41 cases (19.62 %) of non-infectious erythematous papulosquamous diseases, 13 cases (6.22 %) of inflammatory disorders, 10 (4.78 %) cases showed connective tissue disorders. 8(3.83%) cases were reported as vasculitis and 2 cases (0.96) of fungal origin. 18 cases come under the miscellaneous category that was correlated clinically and were treated. Conclusion: In the present study of non-neoplastic skin lesions, non-infectious vesiculobullous diseases were more common. Pemphigus Vulgaris was the most common lesion. The non-neoplastic skin lesions were most commonly seen in males than females in our population of the study.